Proceedings of the Ninth International Symposium on Consumer Electronics, 2005. (ISCE 2005).
DOI: 10.1109/isce.2005.1502350
|View full text |Cite
|
Sign up to set email alerts
|

A study on the transmission characteristics of the human body towards broadband intra-body communications

Abstract: Intra-body communications is becoming a promising solution for Body Area Nefworks with a lot of interesting potential applications towards a ubiquitous communication world. Our research is based on the neurfield radio. wherein electromagnetic radio signals are transmitted through the human bo& from a transmitter to a receiver. In contrast with current studies, we aim to study the transmission characteristics of the human body as a conductor of radio signals with higher frequency carriers (up to 1400MNz) in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…We [6,7,8] have shown that the optimal configuration is composed by transmission and receiver electrodes without ground electrodes and a diameter of 2cm because of the lowest attenuation performed. From a point of view of time delay, the configuration of transmission and receiver electrodes without ground electrodes does not provide the best performance.…”
Section: Fig1 Typical Ibc Transmission Methodsmentioning
confidence: 99%
“…We [6,7,8] have shown that the optimal configuration is composed by transmission and receiver electrodes without ground electrodes and a diameter of 2cm because of the lowest attenuation performed. From a point of view of time delay, the configuration of transmission and receiver electrodes without ground electrodes does not provide the best performance.…”
Section: Fig1 Typical Ibc Transmission Methodsmentioning
confidence: 99%
“…The secondary electric field is radiated from the charge induced on the entire surface of the human body (7). When a human body with a secondary field radiation touches the top of the electrodes embedded in the floor (8), electrostatic induction occurs on top of these electrodes (9). As a result, potential is generated between the receiving electrodes (10).…”
Section: Principle Of Near-field Intrabody Communicationmentioning
confidence: 99%
“…There are various methods of near-field intrabody communication; [1][2][3][4][5][6][7][8][9][10][11][12][13][14] however, to realize communication at a high data transfer rate, the use of a communication system with a quasi-electrostatic field (an electric field) as the communication transmission carrier is promising.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the antenna is one of the key elements in the wireless body area networks. Antennas with omni-directional radiation [9]- [11] in free space and diversity [12]- [16] are commonly used in body area networks However, the radiation patterns will be altered when the antennas are placed near the body. Therefore, by using antennas of different radiation characteristics, the overall system performance can be optimized.…”
mentioning
confidence: 99%